Screening Methanolic Extracts of Sutherlandia spp (Cancer Bush) as Anti- Tumor Agents and their Effects on Anti-Apoptotic Genes: Anti-tumor of Sutherlandia spp - Raymond Motadi, Lesetja (Iranian Journal of Pharmaceutical Sciences, 2020)
In South Africa, cervical cancer is the utmost common cancer in women with an annual crude incidence rate of 30.2 per 100,000 women. Many of home are still dependent on traditional medicine. Because of the name―cancer bush’ given to Sutherlandia frutescens (SF) plant by the traditional healers for its anti-cancer activity, the plant was used lines. MTT and xCELLigence were used to predict the IC50 and evaluate methanolic extract effect on SiHa cell lines. Flow cytometer was used to characterize the cell death type. Caspase 3/7 and ATP assays. MTT and xCELLigence results showed a growth inhibition following treatment with varying concentration of Sutherlandia frutescens with IC50 optimal at 50ug/ml. ATP level increased in S.F treated cells. Flow cytometry showed cells dying by apoptosis and with many cells trapped in S-Phase. Caspase activity was high in methanolic treated cells. The compounds used were: Canavanine, GABA and Pinitol. These compounds induced cell death at the highest concentration used. Sutherlandia frutescens has shown potential to disrupt DNA replication thereby damaging DNA and arresting cell at S-phase leading to cell death by apoptosis.